lim(x趋近于0)(sinx/x)的(1/1-cosx)次方
= lim(x趋近于0)(1+sinx/x -1)的(1/1-cosx)次方
=e的{ lim(x趋近于0)(sinx/x-1)×【1/(1-cosx)】次方}
下解
lim(x趋近于0)(sinx/x-1)×【1/(1-cosx)】
= lim(x趋近于0)(sinx-x)/x(1-cosx)】
= lim(x趋近于0)(sinx-x)/(x*x²/2) (等价代换)
=2 lim(x趋近于0)(sinx-x)/x³
=2 lim(x趋近于0)(cosx-1)/3x²
=2 lim(x趋近于0)(-x²/2)/3x²
=-1/3
所以
原式=e的(-1/3)次方.可这样表示:e^(-1/3)e的{ lim(x趋近于0)(sinx/x-1)×【1/(1-cosx)】次方 这步的)×【1/(1-cosx)】次方 是什么意思?是不是有个"ln"?不需要,有公式的。 lim(1+f(x))^g(x) =e^[limf(x)g(x)]这个公式中x没有限定条件吗?趋近于0或者无穷都可以?f(x)--->0 g(x)---->∞OK谢谢了